Co-translational profiling in the cardiac endothelium in response to LPS-induced inflammation in female mice in vivo: a proof-of-concept approach - Chad M. Warren; Bhairavi Swaminathan; Paulina Langa; Stephanie R. Villa; Walter C. Thompson; Magdalena Chrzanowska; Jan K. Kitajewski; R. John Solaro; Beata M. Wolska; Paul H. Goldspink (Molecular and Cellular Biochemistry, 2026)
Producing functional proteins involves multiple steps during mRNA translation on the ribosomes. However, co-translational regulatory mechanisms remain poorly characterized in intact mammalian systems. As a proof-of-concept, we developed a multi-omics approach to investigate endothelial-specific, co-translational regulation by modifying the translating ribosome affinity purification (TRAP) in vivo. We simultaneously co-immunoprecipitated (IP) polysome-associated mRNAs and proteins from the hearts of hemagglutinin-tagged ribosomal protein L22 mice (RiboTag) crossed with inducible endothelial-specific Cdh5CreERT2 mice ( RiboTag EC ). To perturb endothelial function, female mice were injected with E. coli lipopolysaccharide (LPS) (6 mg/Kg, i.p., 12 h). Hearts were homogenized, with ~ 10% used for input RNA-Seq and proteomics controls, and the remainder for IP of ribosome-bound polyadenylated mRNA and proteins. Endothelial cell transcripts ( pecam1 , cdh5 ) were enriched > 5-fold, while markers characteristic of other cell types were significantly depleted (< 0.05 q-value). We aligned transcriptomic and proteomic datasets (> 1250 overlapping terms) to identify pathways associated with concordant and discordant co-translational regulation. LPS was identified as the upstream regulator of the co-translational dataset that was concordantly regulated. Upregulated mRNAs but not proteins related to glycolysis were discordantly regulated. These findings validate our proof-of-concept multi-omics approach as a predictive platform for identifying disease-relevant pathways regulated at the co-translational level in vivo.

Notch ligands are biomarkers of anti-TNF response in RA patients - Stephanie R. Zack; Anja Meyer; Brian Zanotti; Michael V. Volin; Sania Deen; Neha Satoeya; Nadera Sweiss; Myles J. Lewis; Costantino Pitzalis; Jan K. Kitajewski; Shiva Shahrara (Angiogenesis, 2024)

Notch1 and Notch4 core binding domain peptibodies exhibit distinct ligand-binding and anti-angiogenic properties - Timothy Sargis; Seock-Won Youn; Krishna Thakkar; L. A. Naiche; Na Yoon Paik; Kostandin V. Pajcini; Jan K. Kitajewski (Angiogenesis, 2023)
The Notch signaling pathway is an important therapeutic target for the treatment of inflammatory diseases and cancer. We previously created ligand-specific inhibitors of Notch signaling comprised of Fc fusions to specific EGF-like repeats of the Notch1 extracellular domain, called Notch decoys, which bound ligands, blocked Notch signaling, and showed anti-tumor activity with low toxicity. However, the study of their function depended on virally mediated expression, which precluded dosage control and limited clinical applicability. We have refined the decoy design to create peptibody-based Notch inhibitors comprising the core binding domains, EGF-like repeats 10–14, of either Notch1 or Notch4. These Notch peptibodies showed high secretion properties and production yields that were improved by nearly 100-fold compared to previous Notch decoys. Using surface plasmon resonance spectroscopy coupled with co-immunoprecipitation assays, we observed that Notch1 and Notch4 peptibodies demonstrate strong but distinct binding properties to Notch ligands DLL4 and JAG1. Both Notch1 and Notch4 peptibodies interfere with Notch signaling in endothelial cells and reduce expression of canonical Notch targets after treatment. While prior DLL4 inhibitors cause hyper-sprouting, the Notch1 peptibody reduced angiogenesis in a 3-dimensional in vitro sprouting assay. Administration of Notch1 peptibodies to neonate mice resulted in reduced radial outgrowth of retinal vasculature, confirming anti-angiogenic properties. We conclude that purified Notch peptibodies comprising EGF-like repeats 10–14 bind to both DLL4 and JAG1 ligands and exhibit anti-angiogenic properties. Based on their secretion profile, unique Notch inhibitory activities, and anti-angiogenic properties, Notch peptibodies present new opportunities for therapeutic Notch inhibition.

Unique functions for Notch4 in murine embryonic lymphangiogenesis - Ajit Muley; Minji Kim Uh; Glicella Salazar-De Simone; Bhairavi Swaminathan; Jennifer M. James; Aino Murtomaki; Seock Won Youn; Joseph D. McCarron; Chris Kitajewski; Maria Gnarra Buethe; Gloria Riitano; Yoh-suke Mukouyama; et al. (Angiogenesis, 2022)
In mice, embryonic dermal lymphatic development is well understood and used to study gene functions in lymphangiogenesis. Notch signaling is an evolutionarily conserved pathway that modulates cell fate decisions, which has been shown to both inhibit and promote dermal lymphangiogenesis. Here, we demonstrate distinct roles for Notch4 signaling versus canonical Notch signaling in embryonic dermal lymphangiogenesis. Actively growing embryonic dermal lymphatics expressed NOTCH1, NOTCH4, and DLL4 which correlated with Notch activity. In lymphatic endothelial cells (LECs), DLL4 activation of Notch induced a subset of Notch effectors and lymphatic genes, which were distinctly regulated by Notch1 and Notch4 activation. Treatment of LECs with VEGF-A or VEGF-C upregulated Dll4 transcripts and differentially and temporally regulated the expression of Notch1 and Hes / Hey genes. Mice nullizygous for Notch4 had an increase in the closure of the lymphangiogenic fronts which correlated with reduced vessel caliber in the maturing lymphatic plexus at E14.5 and reduced branching at E16.5. Activation of Notch4 suppressed LEC migration in a wounding assay significantly more than Notch1, suggesting a dominant role for Notch4 in regulating LEC migration. Unlike Notch4 nulls, inhibition of canonical Notch signaling by expressing a dominant negative form of MAML1 (DNMAML) in Prox1+ LECs led to increased lymphatic density consistent with an increase in LEC proliferation, described for the loss of LEC Notch1 . Moreover, loss of Notch4 did not affect LEC canonical Notch signaling. Thus, we propose that Notch4 signaling and canonical Notch signaling have distinct functions in the coordination of embryonic dermal lymphangiogenesis.

Correction to: Notch regulates vascular collagen IV basement membrane through modulation of lysyl hydroxylase 3 trafficking - Stephen J. Gross; Amelia M. Webb; Alek D. Peterlin; Jessica R. Durrant; Rachel J. Judson; Qanber Raza; Jan K. Kitajewski; Erich J. Kushner (Angiogenesis, 2021)
A correction to this paper has been published: https://doi.org/10.1007/s10456-021-09801-w

Notch regulates vascular collagen IV basement membrane through modulation of lysyl hydroxylase 3 trafficking - Stephen J. Gross; Amelia M. Webb; Alek D. Peterlin; Jessica R. Durrant; Rachel J. Judson; Qanber Raza; Jan K. Kitajewski; Erich J. Kushner (Angiogenesis, 2021)
Collagen type IV (Col IV) is a basement membrane protein associated with early blood vessel morphogenesis and is essential for blood vessel stability. Defects in vascular Col IV deposition are the basis of heritable disorders, such as small vessel disease, marked by cerebral hemorrhage and drastically shorten lifespan. To date, little is known about how endothelial cells regulate the intracellular transport and selective secretion of Col IV in response to angiogenic cues, leaving a void in our understanding of this critical process. Our aim was to identify trafficking pathways that regulate Col IV deposition during angiogenic blood vessel development. We have identified the GTPase Rab10 as a major regulator of Col IV vesicular trafficking during vascular development using both in vitro imaging and biochemistry as well as in vivo models. Knockdown of Rab10 reduced de novo Col IV secretion in vivo and in vitro. Mechanistically, we determined that Rab10 is an indirect mediator of Col IV secretion, partnering with atypical Rab25 to deliver the enzyme lysyl hydroxylase 3 (LH3) to Col IV-containing vesicles staged for secretion. Loss of Rab10 or Rab25 results in depletion of LH3 from Col IV-containing vesicles and rapid lysosomal degradation of Col IV. Furthermore, we demonstrate that Rab10 is Notch responsive, indicating a novel connection between permissive Notch-based vessel maturation programs and vesicle trafficking. Our results illustrate both a new trafficking-based component in the regulated secretion of Col IV and how this vesicle trafficking program interfaces with Notch signaling to fine-tune basement membrane secretion during blood vessel development.

Consensus guidelines for the use and interpretation of angiogenesis assays - Patrycja Nowak-Sliwinska; Kari Alitalo; Elizabeth Allen; Andrey Anisimov; Alfred C. Aplin; Robert Auerbach; Hellmut G. Augustin; David O. Bates; Judy R. van Beijnum; R. Hugh F. Bender; Gabriele Bergers; Andreas Bikfalvi; et al. (Angiogenesis, 2018)

PDGFRβ-P2A-CreERT2 mice: a genetic tool to target pericytes in angiogenesis - Henar Cuervo; Brianna Pereira; Taliha Nadeem; Mika Lin; Frances Lee; Jan Kitajewski; Chyuan-Sheng Lin (Angiogenesis, 2017)

In vitro modeling of endothelial interaction with macrophages and pericytes demonstrates Notch signaling function in the vascular microenvironment - Ian W. Tattersall; Jing Du; Zhuangzhuang Cong; Bennet S. Cho; Alyssa M. Klein; Chelsea L. Dieck; Reyhaan A. Chaudhri; Henar Cuervo; James H. Herts; Jan Kitajewski (Angiogenesis, 2016)

A switch in Notch gene expression parallels stem cell to endothelial transition in infantile hemangioma - June K. Wu; Omotinuwe Adepoju; Dinuka De Silva; Keith Baribault; Elisa Boscolo; Joyce Bischoff; Jan Kitajewski (Angiogenesis, 2010)

Chloride intracellular channel 4 is involved in endothelial proliferation and morphogenesis in vitro - Jennifer J. Tung; Oliver Hobert; Mark Berryman; Jan Kitajewski (Angiogenesis, 2009)

Wnt/Frizzled signaling in angiogenesis - Marielba Zerlin; Martin A. Julius; Jan Kitajewski (Angiogenesis, 2008)

Wnt/β-Catenin Signaling Induces Proliferation, Survival and Interleukin-8 in Human Endothelial Cells - T. Néstor H. Masckauchán; Carrie J. Shawber; Yasuhiro Funahashi; Chi-Ming Li; Jan Kitajewski (Angiogenesis, 2005)